Pembuatan Candlenut Gel Dengan Konsentrasi Emulsifier Beeswax Terhadap Mutu Fisik Pelembab - Firrahmah, Syuru (Politeknik Negeri Lhokseumawe, 2024)
Nowadays, more and more skin moisturizing formulations are derived from natural ingredients. One of them is the use of vegetable oils. Vegetable oil is known to contain compounds that can act as an emollient so that it has the potential to be developed as a skin. Therefore, this research aims to determine the optimal conditions of Candlenut gel for dry skin based on natural ingredients and determine the characteristics of moisturizers against the type of addition of candlenut oil oil and the volume concentration of honeycomb as an emulsifier. This research uses heating method with emulsifier variation (beeswax) 2ml, 4ml, 6ml, 8ml and 10ml with candlenut oil variations 2.5ml, 5ml, 7.5ml, 10ml and 10.5ml. From the results of variations in the concentration of honeycomb, the honeycomb emulsifier is obtained at a variation of 8ml with a variation of 5ml candlenut oil.